Determination of 14 aminoglycosides by LC-MS/MS using molecularly imprinted polymer solid phase extraction for clean-up. Issue 4 (3rd April 2018) - Savoy, Marie-Claude; Woo, Pei Mun; Ulrich, Pauline; Tarres, Adrienne; Mottier, Pascal; Desmarchelier, Aurélien
ABSTRACT: An LC-MS/MS method for screening 14 aminoglycosides in foodstuffs of animal origin is presented. Its scope includes raw materials and processed ingredients but also finished products composed of milk, meat, fish, egg or fat. Aminoglycosides are extracted in an acidic aqueous solution, which is first recovered after centrifugation, then diluted with a basic buffer and finally purified by molecularly imprinted polymer-solid phase extraction (MIP-SPE). Analytes are detected within 8 min by ion-pair reversed phase LC-MS/MS. Due to the large range of foodstuffs involved, the variability of matrix effects led to significant MS signal variations. This was circumvented by systematically extracting each sample twice, i.e. 'unspiked' and 'spiked' at the screening target concentration of 50 µg kg −1 . The method was validated according to the European Community Reference Laboratories Residues Guidelines giving false-negative and false-positive rates ≤3% for all compounds. Ruggedness of the method was further demonstrated in quality control operations by a second laboratory. The 14 aminoglycosides in water-based standard solutions were stable for up to 6 months when stored at either −80°C, −20°C or at 4°C storage temperatures.